ПРОБЛЕМЫ И ПЕРСПЕКТИВЫ РЕАЛИЗАЦИИ ПРОГРАММЫ ФОРСИРОВАННОГО ИННОВАЦИОННОГО РАЗВИТИЯ КАЗАХСТАНА (Journal of Economic Research & Business Administration, 2015)
The article is devoted to socio-economic and demographic problems in the context of innovation development of Kazakhstan